Estimation of Government Spending Multiplier in EU Economies - Senekovič, Marko; Kavkler, Alenka; Bekő, Jani (Naše gospodarstvo/Our economy, 2019)
The aim of this paper is to estimate government consumption multiplier and to examine the effect of various characteristics of countries on the size of fiscal multiplier. We apply a panel VAR model following Ilzetzki et al. (2013) for a sample of 28 EU countries covering the period from 1995 to 2017. Key findings are, first, the estimated average fiscal multiplier is larger than unity. Second, the size of fiscal multiplier is larger in the cases of lower public indebtedness, for more developed European countries and for more financially open economies, which is also in line with relevant empirical literature. Regarding the role of trade openness, the results are inconclusive. In addition to this, membership of countries in the European integrations positively affects the size of fiscal multiplier. Therefore, fiscal policymakers should use fiscal stimuli as the instrument of boosting short- term economic growth selectively and consider country-specific characteristics. This paper contributes to the ongoing discussion in two ways, it examines the effect of additional characteristics of countries on the size of fiscal multiplier and updates existing empirical literature.